Commentary on the special issue on ability beliefs and learning a new language at school - Aek Phakiti (Studies in Second Language Learning and Teaching, 2025)
This commentary discusses the important contribution of the special issue on ability beliefs in language learning at school. The nature of language learning is highly complex and requires complex theories to explain its linguistic, cognitive and social phenomena. I am particularly interested in writing a commentary on this special issue, given my long-term intrinsic interest in learning about psychological constructs that influence language learners’ behaviors and performance. This article considers and responds to various ability belief constructs that the authors have presented, such as self-efficacy, self-concepts, and mindsets, as well as factors that contribute to the operation of these constructs in language learning. This article finally reflects on the issues I have learned from this commentary, pointing out exciting avenues for researching ability beliefs in language learning.